“Derecho a la alimentación en el régimen constitucional de la soberanía alimentaria, un análisis desde la perspectiva de las políticas públicas en los países de India y Alemania”. - Carrillo Celi, Adrián Fabricio (2025)
The present research work entitled "RIGHT TO FOOD IN THE CONSTITUTIONAL REGIME OF FOOD SOVEREIGNTY, AN ANALYSIS FROM THE PERSPECTIVE OF PUBLIC POLICIES IN THE COUNTRIES OF INDIA AND GERMANY" refers to the Constitution of the Republic of Ecuador, where food sovereignty in Ecuador refers to the right of individuals to decide on their own food and food production in a sustainable and environmentally friendly manner. This concept aims to promote local food production, access to nutritious and culturally appropriate food, as well as the protection of biodiversity and traditional knowledge. It also emphasizes the responsibility of the State in promoting food sovereignty and ensuring food self-sufficiency for individuals, communities, peoples, and nationalities. It is mentioned that Ecuador currently lacks public policies that guarantee sustainable agriculture, leading to the uncontrolled use of fertilizers and fungicides in agricultural production, causing environmental pollution and harming consumer health. There is a need to implement public policies in the agricultural sector that promote appropriate and sustainable agriculture to ensure the constitutional right to food sovereignty. The following research is based on the importance of the Ecuadorian State implementing public policies that ensure appropriate and sustainable agriculture, preventing malnutrition especially in vulnerable individuals and children under one year of age, as well as diseases related to the consumption of food contaminated with chemicals used in agricultural practices. It highlights the importance of guaranteeing the constitutional right to food sovereignty as it also contributes to the economic and social development of the country, strengthens family farming, and protects the environment. It is a fundamental right that must be protected and promoted by the State to ensure the well-being and dignity of the Ecuadorian population. Keywords: Right, food, sovereignty, policies, public, countries.